synthesis and study of some mixed ligand complexes of caffeine - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
I've been in this research preparation and diagnostic complexes mixed Kandat of Alcavaúan Alpiculan ion Althaaossianat with some metal ions has been reactive in ethanol solvent and distilled water by (1:1) and water complexes and lotions to the accounts of the metal in the complex